Mechanical and morphological characterization of polymer–carbon nanocomposites from functionalized carbon nanotubes - Paiva, M. C. (2004)
Carbon nanotubes were functionalized with poly(vinyl alcohol) (PVA). The water-soluble PVA–functionalized carbon nanotubes were then embedded into PVAmatrix via a wet-casting method, resulting in polymer–carbon nanocomposite films with homogeneous nanotube dispersion. Composites with pristine and functionalized nanotubes were tested in tension. It was found that the mechanical properties of these nanocomposite films were significantly improved compared to the neat polymer film. Functionalization allowed good distribution of the nanotubes in the matrix, leading to higher film strength. Scanning electron microscopy shows an apparent good wetting of the nanotubes by the PVAmatrix. These results are supportive of good interfacial bonding between the functionalized carbon nanotubes and the hosting polymer matrix.